Pengembangan Aplikasi Jaringan dan Dokumentasi Informasi Hukum dengan Metode User Centered Design - Bouty, Abd Azis; Kadim, Ahmad Azhar; Rijal, Bait Syaiful; Tuloli, Mohamad Syafri; Kaharu, Ramadan (Jambura Journal of Informatics, 2023)
The JDIH application used by the Regional Secretariat of the Legal Section of Bone Bolango to manage legal information documentation still lacks features in the application. There is no question and answer feature for the public, the function of the search feature is not good, the application user satisfaction survey is not yet available, and the user interface display is not attractive to users. The research objectives are (1) Designing the JDIH Bone Bolango application according to user needs, (2) Applying the User Centered Design method to the JDIH Bone Bolango application, (3) Knowing the user's response to the JDIH Bone Bolango application. The method used is User Centered Design with 4 stages namely specify context of use, specify user and organizational requirements, design solution, and evaluate design of requirements. System testing uses black box testing and sus methods. Data collection techniques using observation and interviews. The results of the study found that the application developed was in accordance with user needs with the calculation results of the SUS method obtaining a result of 84 with an acceptable level, which means that the application can be accepted and used. Aplikasi JDIH yang digunakan oleh Sekretariat Daerah Bagian Hukum Bone Bolango untuk mengelola dokumentasi informasi hukum masih terdapat kekurangan dalam hal fitur dalam aplikasi. Tidak adanya fitur tanya jawab untuk publik, kurang baiknya fungsi dari fitur pencarian, belum tersedianya survey kepuasan pengguna aplikasi, dan tampilan user interface yang kurang menarik bagi pengguna. Tujuan penelitian yakni (1) Merancang aplikasi JDIH Bone Bolango sesuai kebutuhan pengguna, (2) Menerapkan metode User Centered Design pada aplikasi JDIH Bone Bolango, (3) Mengetahui respon pengguna terhadap aplikasi JDIH Bone Bolango. Metode yang digunakan User Centered Design dengan 4 tahapan yaitu specify context of use, specify user and organizational requirement, design solution, dan evaluate design of requirement. Pengujian sistem menggunakan metode black box testing dan SUS. Teknik pengambilan data menggunakan observasi dan wawancara. Hasil penelitian didapatkan bahwa aplikasi yang dikembangkan sudah sesuai dengan kebutuhan pengguna dengan hasil perhitungan metode SUS mendapatkan hasil 84 dengan tingkat acceptable yang berarti aplikasi dapat diterima dan digunakan.